Time matters: The role of recovery for daily mood trajectories at work - Maike Arnold; Sabine Sonnentag (Journal of Occupational and Organizational Psychology, 2023)
Taking a temporal perspective, we examined how employees' mood (i.e., wakefulness-tiredness, calmness-tenseness, and pleasantness-unpleasantness) develops during the workday and tested employees' daily recovery from work as a predictor of these mood trajectories. Specifically, we analysed a serial mediation model with evening recovery experiences (i.e., psychological detachment, relaxation, mastery experiences, and control) being indirectly related to the development of next-day mood (i.e., linear slopes) via sleep quality and start-of-work mood. We collected data from 124 employees who completed up to 5 daily surveys over two workweeks. Multilevel growth curve models showed that, in general, wakefulness followed a negative quadratic, calmness a positive quadratic, and pleasantness no systematic trajectory during the workday. At the day level, path analyses showed that psychological detachment indirectly and relaxation directly predicted the three start-of-work mood states. Moreover, mastery experiences and control directly predicted start-of-work calmness. Additionally, psychological detachment and relaxation indirectly predicted the development of wakefulness and psychological detachment, relaxation, and mastery experiences indirectly predicted the development of calmness. Results suggest that some benefits of daily psychological detachment, relaxation (i.e., high start-of-work wakefulness and calmness), and mastery experiences (i.e., high start-of-work calmness) tend to subside during the workday.
Keywords: 650; mood; recovery experiences; sleep quality; temporal approach; trajectories